Strategis to Avoid Tax Penalties and Common Errorsin VAT and Income Tax Reporting - Tarigan , Heskyel Pranata; Mw, Rahmat Nurwahid (Tractare: Jurnal Ekonomi-Manajemen, 2025)
Tax compliance is a critical responsibilitu for individuals and busisnesses. Howener, errors in reporting Value-Added Tax (VAT) and Income Tax (PPh) can lead to penalties that negatively impact financial stability. This article outlines strategies to avoid such penalties, including understanding tax obligations, using tax software, meeting deadlines, and avoiding common mistakes such as incorrect calculations or incomplete reporting. It also highlights the importance of consulting tax professionals, maintaining proper documentation, and utilizing available tax incentives. By implementing these strategies, tax reporting can be more accurate, risks can be minimized, and financial management optimized.